Constant current control for regenerative braking of passive series hybrid power system. (19th August 2020) - Pan, Chaofeng; Wang, Jian; Dai, Wei; Chen, Liao; Chen, Long
Summary: Regenerative braking system, widely used in electric vehicle (EV), is the crucial configuration, which converts kinetic energy into electrical energy; therefore, saving electricity to prolong the driving range. As the auxiliary energy source of EVs, the supercapacitor with high current charging and high‐power density reduces the impact of high current charging on the battery during regenerative braking. The analysis of regenerative braking system, with lithium ion battery and supercapacitor, for EVs gives top priority to the structure of passive series connection between supercapacitor and battery. Accordingly, the mathematical model of regenerative braking system with hybrid power source is established, which consists of brushless direct current (DC) motor supercapacitor model and controller. Moreover, the modeling and simulation of regenerative braking system are carried out under Simulink environment. Consequently, current control strategy of regenerative braking, verified by simulation and vehicle testing, has come out. The results show that the hybrid power system, composed with power battery and supercapacitor in series, can effectively absorb the regenerative braking energy, which the control strategy of current for regenerative braking can not only realize the stability of braking current and generate stable regenerative force, but also obtain higher energy recovery rate. Abstract : As the auxiliary energy source of EVs, the supercapacitor with high current charging and high‐power density reduces the impact of high current charging on the battery during regenerative braking. The analysis of regenerative braking system with lithium ion battery and supercapacitor for EVs gives top priority to the structure of passive series connection between supercapacitor and battery.